Dois estudos em análise do comportamento: emergência de leitura após diferentes tipos de ensino de sílabas e palavras e introdução ao letramento analítico-comportamental - MESQUITA, Alex Andrade (Universidade Federal do Pará, 2018)
Reading can be understood as a complex network of relations between stimuli and responses. Study 1 aimed verify the effect of different types of syllable teaching (before or along with the word) and word sizes (two syllables or three syllables) on the development of recombinative and comprehension reading, perform a typology of word naming errors, and verify if the teaching method were considered reinforcing by the participants. The study participants were twelve children aged six to seven years, who were taught to read through the MTS and CRMTS procedure. The results showed that the type of syllable teaching had little influence on the recombinative and comprehension readings, but the participants who learned three syllables words developed a repertoire of recombinative reading superior to those who learned two syllables words and presented fewer errors. The most common type of error was to the exchange of syllables and the syllabication of the word. All children evaluated positively the teaching method. We conclude that the teaching of larger words can facilitate the generalized recombinative reading. In study 2 a bibliographic review of the narrative type was carried out with the objectives of: 1) presenting briefly the most used literacy methods in Brazil; 2) describe literacy in behavioral terms; 3) propose a new behavioral-analytic method of literacy. We verified that the most used literacy methods were: synthetic, with emphasis on the phonic, analytical, whole language, social constructivism and the Paulo Freire method. Quotations to behaviorist methods are few and often negative. Literacy involves complex behavioral processes and it can be reconciled with behavioral analysis as long as the behavioral objectives are clear and preferable immediate differential consequences follow the learning.